Probabilistic analysis of geological and structural Prospects for Oil and gas Potential in Western Yakutia Using three-Dimensional Empirical Mode Decomposition of Potential Fields - D. F. Kalinin; A. S. Dolgal; V. V. Voroshilov (Georesursy, 2024)
Further development of modern formal approaches to extracting geo-structural information from gravimetric and magnetometric data is herein discussed. A practical example of using 3D GEMD (three-dimensional controlled empirical mode decomposition) algorithm to calculate potential fields transforms associated with the impact of deep and medium (of different ranks) geological structures on the adjacent territories of Western Yakutia was considered. Two types of reference groups were determined based on analysis of the known hydrocarbon fields in the Lena-Vilyuy and Lena-Tunguska oil and gas provinces. Statistical efficiency of the observed fields, fields’ area transforms (modified functions of empirical decomposition), and also spatially-linked combinations of the said attributes, aiming to solve the forecasting tasks, was determined. As a result of integration within the testing area, layout diagrams of deep geological and structural prerequisites for oil and gas potential, similar to group standards, were drawn up. A geological interpretation of forecasting and geophysical constructions is presented. It is shown that a number of identified areas predicted with high probabilities correlate with depressions of rift zones. Combined with thick volcanogenic-sedimentary formations, the latter forms most prospective oil and gas content pre-requisites.